Integrasi Nilai-Nilai Islam dalam Pendidikan Karakter di Sekolah SMPN 2 Rangsang Pesisir - Badriyah, Miftahul Shulha (Jurnal Pendidikan Islam Indonesia, 2025)
This study aims to examine the integration of Islamic values in character education at SMPN 2 Rangsang Pesisir and its impact on students’ behavior and attitudes. The Islamic values analyzed include religiosity, honesty, discipline, responsibility, and mutual respect, which are implemented in the learning process and school culture. The research employed a qualitative method with a descriptive approach. Data were collected through observation, in-depth interviews with the principal, Islamic Education teachers, and students, as well as documentation of school-related activities. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results indicate that the integration of Islamic values at SMPN 2 Rangsang Pesisir has been implemented through classroom learning activities, habituation of worship practices, teachers’ role modeling, as well as religious programs and school regulations. This integration contributes positively to shaping students’ character, particularly in improving discipline, politeness, responsibility, and religious awareness. However, several challenges remain, such as the influence of the external environment and differences in students’ backgrounds, indicating the need for continuous efforts and collaboration among schools, teachers, and parents.